Cancer information overload: Association between a brief version of the CIO scale and multiple cancer risk management behaviours. Issue 5 (May 2021) - Breyton, Martin; Smith, Allan Ben; Rouquette, Alexandra; Mancini, Julien
Highlights: The 5-item CIO scale is ready to be used in French and English-speaking countries. It can be used in cancer survivors, caregivers and healthy subjects. CIO is associated with multiple unhealthy behaviours but not with alcohol misuse. CIO might help to evaluate cancer information messages provided. Abstract: Objectives: To demonstrate the best psychometric properties of the revised 5-item Cancer Information Overload (CIO) scale over the 10- and 8-item versions, for both English and French native speakers, and to explore the relationships between CIO and several cancer risk management behaviours in a large sample of caregivers, cancer survivors and healthy subjects. Methods: 2809 participants (2568 from France, 241 from Australia) from two cancer survivor networks answered a self-administered questionnaire. After assessing the psychometric properties we studied the impact of CIO on health behaviours using multivariate logistic regression. Results: Internal consistency assessment and Confirmatory Factor Analysis (CFA) showed satisfactory results ( α  = 0.87 and 0.83, ω  = 0.87 and 0.83, RMSEA = 0.078 and 0.081 for the 8-item and 5-item versions respectively), as well as multi-group CFA where measurement invariance was partial for one item only in each version. CIO was independently associated with smoking, sunburns, and rare skin checks, but not with alcohol misuse. Conclusion: The 5-item version of the CIO scale showed adequate psychometric properties and discriminant association with multiple prevention behaviours. Practice implications: The 5-item CIO scale is valid and can help push research forward in the domain of disease prevention and message acceptance. Its role in clinical practice remains to be determined.